Deformation of surrounding rocks in salt caverns in compressed air energy storage plants: insights from laboratory experiments and numerical simulations - Li, Zongze; Wang, Yifan; Fan, Jinyang; Zou, Yang; Chen, Jie; Jiang, Deyi; Nelias, Daniel (Tunnelling and underground space technology, 2026)
The long-term mechanical stability of surrounding rock in compressed air energy storage (CAES) salt caverns is crucial for the safe and efficient operation of underground energy systems. In this study, the deformation behavior of salt rock was investigated through a combined approach that involved long-term laboratory creep-fatigue tests and engineering-scale numerical simulations. Mechanical experiments were carried out at various cyclic stress levels and loading rates to replicate the creep-fatigue loading conditions that are encountered during CAES operations. The results indicate that both the magnitude and the frequency of cyclic loading significantly influence the time-dependent deformation of salt rock: higher stress levels accelerate damage, whereas lower loading rates lead to increased plastic strain. On the basis of the geological conditions of a planned CAES facility, numerical simulations were conducted using FLAC3D. The model incorporates the Norton creep law to simulate the evolution of the surrounding rock with different numbers of operational cycles and gas pressures. The operating pressure and frequency significantly affect the deformation and plastic zone distribution of the surrounding rock in salt cavern reservoirs. Higher operational frequencies and minimum gas pressures result in reduced deformation and improved cavern stability. For the first time, a direct qualitative analysis was conducted to compare the laboratory experiments and numerical simulation results. Comparative analysis reveals that the experimental and simulation results are generally consistent. These findings offer new insights into the mechanical response of salt cavern-surrounding rock and establish a foundation for predicting the long-term performance of CAES systems.
Online verfügbar: 5. Dezember 2025
Gesehen am 11.02.2026